Edukasi Zat Pewarna Pangan Berbahaya Di SMA Negeri 1 Sukadana - Doni Setiawan; Rivana Ariyadi; Euis Tia Istianah; Aldi Febriansyah; Amanda Tyas Zaharani; Chintya Nur Aeni; Desry Delia Futri; Dinda Putri Stevani; Firdaus Nur Rohman; Hayfa Azkal Azkiya; levi Ayu Ramadhanty; Mitha Silvyana; Nailah Ghaissani Dwi Gustari; Nuraisyah Kurniawan; Putri Laksmi Margarethi; Risma Risma; Taopik Cahyadi (LPPM STIKes Muhammadiyah Ciamis, 2023)
Introduction: In general, food coloring can be obtained from natural dyes and safe synthetic food dyes. Natural dyes are sometimes considered less stable and less durable than synthetic food dyes. Although there are synthetic dyes that are safe for food, there are still people who use materials that are not suitable for use in food. The use of harmful food dyes must be monitored and recognized for their existence. Harmful food dyes that are commonly found are textile dyes such as Rhodamine B or methanyl yellow. Because it is not a proper food coloring, consumption of foods containing this ingredient can cause a series of health problems for those who consume it, especially in a relatively long period of time. This education aims to allow students to distinguish foods that use natural coloring agents and artificial coloring agents. The results of this activity students can find out the characteristics of foods that use harmful dyes and know the prevention that can be done. Objective: The purpose of this service is for SMAN 1 SUKADANA students to know the dangers of using hazardous coloring agents in food. Method: The method used is providing education by providing material to students, tests before and after material on the Use of Harmful Coloring Substances in Food. Result: Increased knowledge and attitudes of students are tested through pre-test and post-test. There has been an increase in knowledge in students about the dangers of using harmful dyes in food in general by 20%, so that the realization of the purpose of this service is expected to be able to distinguish food ingredients that contain harmful coloring agents in food and those that do not contain harmful coloring agents in food. Basically, knowledge and attitudes also depend on the high or low level of education of students. Therefore, the existence of this counseling can help students in adding insight into the dangers of using harmful dyes. The implementation of this activity can run well due to positive support in the implementation process, where support from various parties and there are no obstacles whatsoever. Conclusion: The socialization activity on the use of dangerous coloring substances in food to students at SMAN 1 Sukadana received a good response from the school and also students. With outreach activities regarding this, students will understand and be more careful in choosing food to avoid these chemicals.